Role of Ca in Ni-Ca/Fumed-SiO2 Catalysts for CO2 Catalytic Conversion to Methane - Ahmed Aheed Ali Mohammed (22155979) (2024)
This study investigates the role of calcium in facilitating the carbon dioxide methanation reaction over nickel supported on fumed-SiO2 catalysts. The wet impregnation method was used to prepare Ni/fumed-SiO2 catalysts with three different Ca loadings for CO2 conversion. As part of the investigation into the effects of Ca concentration and reaction conditions on the structural and morphological properties of the catalysts, various techniques including XRD, BET, SEM, TPR and TEM were used for both fresh and used catalyst samples. The findings showed that the addition of 0.5% Ca increases the catalyst reducibility, promotes dispersion of Ni sites on the surface of fumed SiO2 support and prevents the metal from agglomerating. Evaluation of catalytic results showed that the performance of 10%Ni-0.5Ca/fumed-SiO2 was superior to the other tested catalysts, with CO2 conversion and CH4 yield of 76% and ~ 40% at 650 °C, respectively. Other Information Published in: Topics in Catalysis License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11244-024-02010-x